Bridging the Gap From Biomechanics and Functional Morphology of Plants to Biomimetic Developments - Speck, Olga; Speck, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the biomimetic and bioinspired developments based on the biomechanical and morphological studies of plants and animals. The articles cover basic research in biology, the modeling of functional principles and the transfer into bioinspired materials systems, as well as hands-on models for teaching and education.